The Influence of Group Affiliation and Ownership Structure on Emerging Market IPOs: The Case of the Philippines - Sullivan, Michael J. (Animo Repository, 1999)
In this paper we report initial returns and long-run performance of IPOs in the Philippines over the period 1987-1997. Within this context we investigate the differential effects on IPO returns of offer size, firm age, industry, market timing, ownership structure, and company affiliation. We find average initial returns of 22.69% for a sample of 104 company IPOs over an 11-year period, 1987 through 1997, and three-year aftermarket adjusted returns of -5.44% for a subset of 65 of these companies. Factors commonly found to affect the level of IPO underpricing are not found significant in the Philippines. Instead, we find that firms affiliated with a corporate group are subject to greater IPO underpricing than unaffiliated firms. We attribute this to affiliated firms issuing IPOs accompanied by a lower degree of information disclosure.